PENGARUH PENGGUNAAN MEDIA MICROSOFT POWERPOINT TERHADAP HASIL BELAJAR MATEMATIKA SISWA SD - Salahuddin, M.; Margiati, K.Y.; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aims to determine the use of Media Microsoft Powerpoint to the students learning outcomes of mathematics of grader III SDN 36 Pontianak South. The research method used is quasi experimental method with non- equivalent control group design. The number of research subjects 63 students. Tool of data collection used is in the form of essay test eight questions. The result of this research is the average of pre-test of experiment class is 69,067 while control class is 72,23. The average post-testof the experimental class is 80.65 and the control class is 75.81. From result of t test, obtained tarithmeticequal to 1,33 with ttable 1,67078 it means tarithmetic< ttable concluded that there is difference of students’ learning outcome. Based on the calculation of effect size (ES), concluded that ES is 0.308. This means that the use of microsoft powerpoint media impact a low effecton the students’ learning outcome of mathematics of grader III SDN 36 Pontianak Selatan. Keywords: Effect, Microsoft Powerpoint, Learning outcome.